The Fulfillment of Religious Education Services for Wong Sikep Samin in Kudus Central Java: A Study From Human Governance Perspectives - Fikhi Yusfita; Ismi Dwi Astuti Nurhaeni (Jurnal Borneo Administrator, 2022)
There are many studies on religious education services. Still, these studies do not use a human governance approach that focuses on respecting human rights and meeting the needs of all citizens. This research aims to analyze the fulfilment of religious education services for the indigenous religious believer, Sedulur Sikep, in Undaan, Kudus. The data was obtained through in-depth interviews and literature studies and analyzed through a qualitative descriptive approach. The informants are the Sedulur Sikep Community in Undaan, Elementary School (SD) 3 Kaliyoso, the Youth and Sports Education Office of Kudus Regency, eLSa (Institute for Social and Religious Studies), and MLKI (Supreme Assembly of Indonesian Belief) Central Java. Sampling was carried out purposively and snowball, and the analysis technique used analysis according to Miles & Huberman. The result indicates that until now, the students of Sedulur Sikep have not received their right to religious education services in formal schools based on The Regulation of The Minister of Education and Culture (Permendikbud) Number 27 of 2016 on Educational Services Belief in God Almighty in Education Units. Instead, they were asked to choose whether to follow Islamic religious education or not follow it at all. Schools do not understand the content of Permendikbud Number 27 of 2016 substantively. The school has not coordinated with the Youth and Sport Education Office of the Kudus Regency and is not trying to collaborate with institutions that handle belief education services. The school must fulfil the right of Sedulur Sikep students to get their rights in religion education services